Kepatuhan Penggunaan Obat pada Pasien Hipertensi di Puskesmas - Saepudin, .; Padmasari, Siwi; Hidayanti, Puri; Ningsih, Endang S (Jurnal Farmasi Indonesia, 2013)
In addition to antihypertensive regimen, medication adherence plays an important role in therapeutic management of hyperensive patients. This research is aimerd to measure adherence to antihypertensive therapy in hypertensive patients at primary health center, and to investigate patient's characteristic associated with such adherence. Hypertensive patients attending two primary health centers in Sleman Yogyakarta during January-March 2011 were recruited as respondents in this research. Adherence to natihypertensive therapy was measured using MMAS (Morisky Medication Adherence Scale) containing 8 questions, and a respondent with MMAS score â?¥Â 6 was categorized as adherent one. Statistical analysis using Chi-square has been done to investigate respondent characteristic associated with adherence. Out of 215 recruited respondents, 62.3% were adherent to antihypertensive therapy. Respondent characteristic associated with adherence are educational background level, monthly income, presence of other chronic disease, and antihypertensive regimen.Keywords : hypertension, medication sdherence, MMAS, primary health center